Searching for Security : Women's Responses to Economic Transformations. - Baud, Isa (Routledge studies in development and society., 2014)
Human Security is a development buzzword of the 1990s. To attain security people need to be safe from natural disasters, such as famine, and 'man-made' problems, such as unemployment. Women are a particularly insecure section of society with the impact of deprivation disproportionately shouldered by women throughout the developing world. Searching for Security examines how economic, political and environmental factors have contributed to increased gender insecurity in the last decade. Analyzing the impacts of insecurity-inducing global changes on the lives of women throughout the.